Informed Consent Documentation for Lumbar Puncture in the Emergency Department - Patel, Pankaj B. (Department of Emergency Medicine, University of California, Irvine, 2014)
Introduction: Informed consent is a required process for procedures performed in the emergency department (ED), though it is not clear how often or adequately it is obtained by emergency physicians. Incomplete performance and documentation of informed consent can lead to patient complaints, medico-legal risk, and inadequate education for the patient/guardian about the procedure. We undertook this study to quantify the incidence of informed consent documentation in the ED setting for lumbar puncture (LP) and to compare rates between pediatric (<18 years) and adult patients. Methods: In this retrospective cohort study, we reviewed the ED electronic health records (EHR) for all patients who underwent successful LPs in 3 EDs between April 2010 and June 2012. Specific elements of informed consent documentation were reviewed. These elements included the presence of general ED and LP-specific consent forms, signatures of patient/guardian, witness, and physician, documentation of purpose, risks, benefits, alternatives, and explanation of the LP. We also reviewed the use of educational material about the LP and LP-specific discharge information. Results: Our cohort included 937 patients; 179 (19.1%) were pediatric. A signed general ED consent form was present in the EHR for 809 (86%) patients. A consent form for the LP was present for 524 (56%) patients, with signatures from 519 (99%) patients/guardians, 327 (62%) witnesses, and 349 (67%) physicians. Documentation rates in the EHR were as follows: purpose (698; 74%), risks (742; 79%), benefits (605; 65%), alternatives (635; 68%), and explanation for the LP (57; 6%). Educational material about the LP was not documented as having been given to any of the patients and LP-specific discharge information was documented as given to 21 (2%) patients. No significant differences were observed in the documentation of informed consent elements between pediatric and adult patients. Conclusion: General ED consent was obtained in the vast majority of patients, but use of a specific LP consent form and documentation of the elements of informed consent for LP in the ED were suboptimal, though comparable between pediatric and adult patients. There is significant opportunity for improvement in many aspects of documenting informed consent for LP in the ED. [West J Emerg Med. 2014;15(3):318–324.]